China: The New Powerhouse of Hormesis Research? - Evgenios Agathokleous (SAGE Publishing, 2021)
More than one third of the worldwide hormesis research has been produced at institutions in the United States (US). Although the US ranked first in terms of hormesis publication records from the mid. 1980s to the mid-late 2010s, China became the largest producer of hormesis publications in the years 2019-2020. As China is transforming into a powerhouse of hormesis research, new opportunities might arise for the research field.